A chromosome-level genome assembly of an alpine plant Crucihimalaya lasiocarpa provides insights into high-altitude adaptation. (29th January 2022) - Feng, Landi; Lin, Hao; Kang, Minghui; Ren, Yumeng; Yu, Xi; Xu, Zhanpeng; Wang, Shuo; Li, Ting; Yang, Wenjie; Hu, Quanjun
Abstract: It remains largely unknown how plants adapt to high-altitude habitats. Crucihimalaya (Brassicaceae) is an alpine genus occurring in the Qinghai–Tibet Plateau characterized by cold temperatures and strong ultraviolet radiation. Here, we generated a chromosome-level genome for C. lasiocarpa with a total size of 255.8 Mb and a scaffold N50 size of 31.9 Mb. We first examined the karyotype origin of this species and found that the karyotype of five chromosomes resembled the ancestral karyotype of the Brassicaceae family, while the other three showed strong chromosomal structural variations. In combination with the rough genome sequence of another congener ( C. himalaica ), we found that the significantly expanded gene families and positively selected genes involved in alpine adaptation have occurred since the origin of this genus. Our new findings provide valuable information for the chromosomal karyotype evolution of Brassicaceae and investigations of high-altitude environment adaptation of the genus.